Water Filter Design Using the Quality Function Deployment (QFD) Method in Cibiru District - Aditya, Sopyan; Yulianti, Dini; Bhagya, Tombak Gapura (Universitas Insan Cendekia Mandiri, 2025)
Clean water is a basic need that cannot be separated from human life. PDAM Tirtawening is only able to fulfill 34.28 percent of the clean water needs of the people of Bandung City. For the other 65.72 percent of Bandung City residents, groundwater is one of the alternatives for residents of Bandung City whose areas do not have flow from the PDAM, as is the case in the Cibiru area of Bandung City. Groundwater conditions in the Cibiru area are divided into 2 groups, namely the ion exchange group & the simple dissolution or mixing group (groundwater undergoes a mixing process) so that the condition of the groundwater is yellow and smells so that it requires a water filter to purify the water. Behind the importance of this water filter lurks the danger if it is not cleaned regularly. The obstacles found in the field are that the water filter cleaning process is still manual, the water filter is not cleaned regularly due to the position of the water filter placement, forgetting to clean and the cleaning process is not practical. The focus of this research is to find out the needs of water filter users (user requirements) and the problems faced by water filter users in the Cibiru area. Researchers used the Quality Function Deployment (QFD) method to redesign a more effective water filter according to the needs of residents in the Cibiru area of Bandung City. The results of the research using the QFD method obtained 7 service attributes needed by consumers and translated into 13 technical requirements in the House Of Quality (HOQ) and 12 priority ranking of water filter designs in the Quality Function Deployment (QFD) table and obtained a new water filter design with a self cleaning system and can be easily disassembled.